Risk management practices in Moroccan participative banks - SEIDA , Mohamed; KERRAOUS , El Mehdi; EL AAROUBI , Siraj (Revue du contrôle, de la comptabilité et de l’audit, 2022)
There is a theoretical debate on risk management efficiency in participative banks compared to their conventional counterparts. Moreover, there are not many empirical studies on this problem. Hence, additional research is necessary to answer this question. The objective of this paper is to explore and analyze the risk and risk management practices in the participative banking industry through the perceptions and the opinions of participants from banking and financial industry. Using a survey on a sample composed of 65 participative and conventional banks and 10 interviews with conventional and participative banks as well, we found that participative and conventional bankers have similar perceptions of risk management. However, participative banks may be riskier than conventional banks because of the additional risks that they face, but also the constraints of this sector regarding risk management. Unfortunately, we note that risk management techniques in participative banks are not as sophisticated as in conventional banks.